Effects of Salbutamol and Furosemide in The Treatment of Transient Tachypnea of Newborn - A Randomized Controlled Trial - Khushdil, Arshad; Ahmed, Zeeshan; Ahmed, Madiha; Nazir, Sajid; Waqar, Talal (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess and compare the effect of Salbutamol and Furosemide therapy in the management of transient tachypnea of newborn. Study Design: Randomized controlled trial (Registered with Clinical Trials.gov: NCT03208894). Place and Duration of Study: Neonatal Intensive Care Unit of Pakistan Emirates Military Hospital Rawalpindi from Oct 2019 to May 2020. Methodology: A total of 100 newborns were included in the study. They were divided into 4 groups. Group-A received nebulized 0.1ml Salbutamol. Group-B was given single intravenous dose of injection Furosemide at the dose of 2mg per kg. Group-C received both IV Furosemide and nebulized Salbutamol. Control group-D received only supportive care. Results: There were 48 male babies and 52 female babies. The average gestational age was 38.8 ± 6.2 weeks and the average birth weight was 2558 ± 620 grams. Administration of both Salbutamol and IV Furosemide together (group-C) showed significant reduction in the mean duration of oxygen dependency compared to control-group (13.40 ± 3.342 vs 83.64 ± 68.546 hours respectively (p<0.001), as well as the need for mechanical ventilation. The mean duration of oxygen dependency in other two groups (A and B) were also reduced compared to control group, but the results were not statistically significant. Conclusion: Salbutamol and Furosemide when given together tend to reduce the duration of oxygen dependency and need for invasive mechanical ventilation in babies with transient tachypnea of newborn.